Applicability of microdialysis as a technique for pharmacokinetic- pharmacodynamic (PK-PD) modeling of antihypertensive beta-blockers - Höcht, Christian (2005)
Introduction: The aim of the present work was to examine microdialysis as a technique for the study of pharmacokinetic-pharmacodynamic modeling of antihypertensive drugs. For this purpose, we studied the antihypertensive and the chronotropic effect of metoprolol and its plasma concentrations in sham operated (SO) and aortic coarctated (ACo) rats at an early hypertensive stage. Methods: Plasma metoprolol concentrations were obtained by means of a "shunt" vascular microdialysis probe. Changes in mean arterial pressure and heart rate were also measured in the same experiment. Results: A rapid decay of metoprolol levels was observed in both experimental groups. For the chronotropic effect, a good association between plasma levels and the chronotropic effect was observed in SO and ACo rats. ACo rats had a greater sensitivity to the chronotropic effect (Emax:-38±2%, n=5, p<0.05) than SO animals (Emax:-27±1%, n=5). A delay in the blood pressure reduction induced by metoprolol was observed in both experimental groups. A good association was observed between concentrations of metoprolol in the effect compartment and the corresponding hypotensive effect in both experimental groups. The calculated PK-PD parameters were not different between SO and ACo groups. Discussion: A good correlation was found between metoprolol concentration and its chronotropic and antihypertensive effects in normotensive and ACo hypertensive rats, allowing the employment of PK-PD models. The microdialysis technique allows simultaneous determination of plasma levels of antihypertensive drugs and their cardiovascular effects, and is therefore a powerful tool for PK-PD modeling.